ChemInform Abstract: Ethoxide‐Mediated Condensation of γ‐tert‐Butylallenoate and Aldehydes: Facile Stereoselective Synthesis of Conjugated Dienes and Enynes. Issue 4 (January 2015) - Xu, Silong; Wang, Liyi; Tang, Yuhai; He, Zhengjie
Abstract Condensation of aldehydes (II) with allenoate (I) in the presence of sodium ethoxide (III) affords dienes (IV) with exclusive E, E‐selectivity.